Optimizing nitrogen removal in advanced wastewater treatment using biological aerated filters - Li, Juan; Niu, Ziru; Li, Lei; Zhou, Shuting (Frontiers in Bioengineering and Biotechnology, 2024)
Reducing total nitrogen (TN) presents a significant challenge for numerous wastewater treatment facilities. In order to address this issue, the current study employed a biological aerated filter for the treatment of wastewater containing low nitrogen concentrations. Both lab-scale and pilot-scale biofilters were constructed to investigate the denitrification performance and maximum denitrification load. The findings indicated that the anaerobic denitrification process of established biofilm adhered to pseudo-first-order kinetics. The results of batch testing and continuous-flow experiments confirmed that the minimum hydraulic retention time (HRT) required for mature biofilm was determined to be 0.5 hour. The optimal operating parameters were found to be as follows: influent NO 3 --N concentration of 25 mg/L, HRT of 0.5 hour, resulting in effluent TN levels below 1 mg/L. Under these conditions, the denitrifying load for the lab-scale I-BAF system was calculated to be 1.26 kg (TN)/( m 3 • d). Furthermore, it was observed that the maximum denitrifying load could reach 2.2 kg (TN)/( m 3 • d) when the influent NO 3 --N concentration was increased to 50 mg/L while maintaining an HRT of 0.5 hour. For the mature biofilter, the appropriate HRT ranged from 2 hours to 0.5 hour. Microbial diversity analysis revealed that the genus Enterobacter was dominant in all denitrification systems, followed by Comamonas and Rhodococcus. The operational parameters described in the paper could be recommended for a full-scale wastewater treatment facility.